The Palgrave Handbook of Race and Ethnic Inequalities in Education 2019
DOI: 10.1007/978-3-319-94724-2_20
|View full text |Cite
|
Sign up to set email alerts
|

Norway: Ethnic (In)equality in a Social-Democratic Welfare State

Abstract: This chapter offers a systematic review of social science research in Norway on ethnic inequalities in education, from the period 1980–2017. Three broad research traditions are identified: (1) Ethnic inequalities in educational enrolment, achievement, and attainment; (2) Immigrant families and ethnic minority communities as resources for educational careers; and (3) Curriculum, teacher instruction, and student experiences with inclusion and exclusion. Most of the research conducted in Norway focuses on describ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 81 publications
0
26
0
2
Order By: Relevance
“…These aspects of the Norwegian educational system appear to provide children of immigrants from low-income families with substantial opportunities for social mobility (Hermansen 2016). Although second-generation pupils achieve somewhat lower grades in secondary school compared to their native majority peers, children of immigrants complete upper secondary school on par with the majority and have higher continuation rates into tertiary education in Norway (Reisel, Hermansen, and Kindt 2019). The second generation is also overrepresented in high-status educational fields such as medicine, law, and economics (Østby and Henriksen 2013).…”
Section: Immigration and The Norwegian Welfare Statementioning
confidence: 99%
See 1 more Smart Citation
“…These aspects of the Norwegian educational system appear to provide children of immigrants from low-income families with substantial opportunities for social mobility (Hermansen 2016). Although second-generation pupils achieve somewhat lower grades in secondary school compared to their native majority peers, children of immigrants complete upper secondary school on par with the majority and have higher continuation rates into tertiary education in Norway (Reisel, Hermansen, and Kindt 2019). The second generation is also overrepresented in high-status educational fields such as medicine, law, and economics (Østby and Henriksen 2013).…”
Section: Immigration and The Norwegian Welfare Statementioning
confidence: 99%
“…As they predominantly grew up in low-income families, they typically lived in less affluent and more immigrant-dense neighborhoods, where they enrolled in the local school. Thus, as is often the case for children of immigrants (Reisel, Hermansen, and Kindt 2019), they started their educational trajectory without ready access to "good schools." However, while parents' economic resources and the residential neighborhood determined access to schools at a lower level, at the upper secondary level, informants could apply to any school within the city and compete for admission based on their grades.…”
Section: Access and Choice: Going To "Bad" Schoolsmentioning
confidence: 99%
“…Unmeasured factors such as one's own educational aspirations or parental expectations regarding one's educational attainment could contribute to understanding the underlying mechanisms of the association between mental disorder and school completion. For instance, Reisel, Hermansen, and Kindt (2019) suggested that research based on registry data could benefit from including survey-based data on ambitions, motivations and mechanisms that drive adolescents when it comes to educational choices and academic achievements. Other research also pinpointed such factors as possible confounders in the association between health and educational outcomes ( Lynch & von Hippel, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…Barn av innvandrere ser ut til å gifte seg senere, få barn senere og få faerre barn enn foreldregenerasjonen (Tønnessen, 2014). Etterkommere av innvandrere fra Sør-Asia tar høyere utdanning i mye større grad enn foreldregenerasjonen (Askvik, 2019;Olsen, 2016;Reisel, Hermansen & Kindt, 2019). Forskjellene i inntekt mellom etterkommere og majoritetsbefolkningen er mindre enn for foreldregenerasjonen, og inntektsnivået for norskfødte med innvandrerforeldre naermer seg det nivået vi finner i majoritetsbefolkningen (Hermansen, 2015).…”
Section: Bakgrunnunclassified